2000
DOI: 10.1073/pnas.97.2.871
|View full text |Cite
|
Sign up to set email alerts
|

ATM is a cytoplasmic protein in mouse brain required to prevent lysosomal accumulation

Abstract: We previously generated a mouse model with a mutation in the murine Atm gene that recapitulates many aspects of the childhood neurodegenerative disease ataxia-telangiectasia. Atm-deficient (Atm؊͞؊) mice show neurological defects detected by motor function tests including the rota-rod, open-field tests and hindpaw footprint analysis. However, no gross histological abnormalities have been observed consistently in the cerebellum of any line of Atm؊͞؊ mice analyzed in most laboratories. Therefore, it may be that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 24 publications
7
103
4
Order By: Relevance
“…This finding is consistent with an involvement of AP-3 in the targeting of membrane proteins to lysosomes. We detected the AP-3 cargo proteins LAMP 1, 2, and TI-VAMP/VAMP7 (Bonifacino and Traub, 2003;Martinez-Arca et al, 2003), an AP-3-interacting protein that regulates lysosome content (ATM) (Lim et al, 1998;Barlow et al, 2000), proteins related to pigment dilution genes (vps33b) (Stepp et al, 1997), and gene products affected in pigment dilution/HermanskyPudlak syndrome (BLOC I subunits pallid, muted, SNA-PAP, and dysbindin/sandy) (Dell'Angelica, 2004). The presence of BLOC1 in AP-3-derived vesicles provides a mechanistic explanation to the overlapping phenotypes observed in mice and humans harboring mutations in either AP-3 or BLOC I subunits (Dell'Angelica, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with an involvement of AP-3 in the targeting of membrane proteins to lysosomes. We detected the AP-3 cargo proteins LAMP 1, 2, and TI-VAMP/VAMP7 (Bonifacino and Traub, 2003;Martinez-Arca et al, 2003), an AP-3-interacting protein that regulates lysosome content (ATM) (Lim et al, 1998;Barlow et al, 2000), proteins related to pigment dilution genes (vps33b) (Stepp et al, 1997), and gene products affected in pigment dilution/HermanskyPudlak syndrome (BLOC I subunits pallid, muted, SNA-PAP, and dysbindin/sandy) (Dell'Angelica, 2004). The presence of BLOC1 in AP-3-derived vesicles provides a mechanistic explanation to the overlapping phenotypes observed in mice and humans harboring mutations in either AP-3 or BLOC I subunits (Dell'Angelica, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This is substantiated, in part, by the experimental data showing that 1) the EL system can be up-regulated in response to the repair mechanisms resulting from cumulative aging, genetic, oxidative, and chemical factors 11,49,50 ; 2) activation of the lysosomal system can restore chloroquine-induced abnormal protein deposits and synaptic decline in hippocampal slice preparation 51 ; and 3) neurons that are not susceptible to death in animal models of neurodegeneration and Alzheimer's disease pathology exhibit increased activation of the EL system. 50,52,53 However, it is of interest to note that the frontal cortex, a region less severely affected by 192-IgG-saporin treatment, showed an up-regulation of the CI-MPR but no significant alterations in Rab5 or LAMP2 as observed in the septum/DBB. Because CI-MPR can mediate multiple functions including cell signaling and internalization leading to degradation/activation of various molecules (ie, IGF-II, leukemia inhibitory factor, and latent transforming growth factor-␤), 1,2,5,6,9,10 it is likely that cortical receptors after the immunotoxin treatment may participate in other functions in addition to regulation of the EL system.…”
Section: Loss Of Cholinergic Neurons and Ci-mpr 1149mentioning
confidence: 99%
“…However, the question of whether the neurodegeneration observed in AT patients results from a loss of this DNA damage response function of ATM has been controversial, since several authors have found that ATM protein is located in the cytoplasm of Purkinje neurons in the human [9] and rodent [10,11] brain. Recently however, Shiloh and co-workers [12,13] found that the ATM protein is present in the nucleus of neuronal derived human cells maintained in tissue culture.…”
Section: Introductionmentioning
confidence: 99%